Uji Efektivitas Spray Repellent Minyak Atsiri Serai Wangi (Cymbopogon nardus L.) pada Nyamuk Aedes aegypti - Handayani, Ratna Fitriana; Rahmawati, Riana Putri; Besan, Emma Jayanti (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
There are two commonly known types of lemongrass, namely kitchen lemongrass (Cymbopogon citratus) and fragrant lemongrass (Cymbopogon nardus L.), both of which are widely used by the community as traditional medicine. This study focuses on fresh fragrant lemongrass, in which the stems are utilized to produce a spray preparation that functions as a mosquito repellent. The study aims to evaluate the effectiveness of fragrant lemongrass essential oil formulated as a spray with different concentrations of 5%, 10%, and 15%. The essential oil of fragrant lemongrass is obtained using the steam distillation method. Prior to formulation into a spray, phytochemical screening was conducted to identify the presence of flavonoids, tannins, saponins, and terpenoids. After completing the phytochemical screening, spray formulations were prepared and divided into three formulation groups. Each formulated spray was evaluated for physical properties, including organoleptic characteristics, pH value, clarity, and homogeneity. In addition, an activity test of the repellent spray was carried out using mosquito test animals. The results showed that the citronella essential oil spray (Cymbopogon nardus L.) exhibited an average repellent power of 61.6% in formulation I, 81.40% in formulation II, and 81.41% in formulation III. The protection power test indicated that the highest repellent activity was observed in formulation III. Based on the One Way ANOVA analysis followed by a Post Hoc test, there was no significant difference between formulation II and formulation III. These findings support the potential use of citronella spray as repellent.